2011
DOI: 10.1002/path.2839
|View full text |Cite
|
Sign up to set email alerts
|

Senescent mesenchymal cells accumulate in human fibrosis by a telomere‐independent mechanism and ameliorate fibrosis through matrix metalloproteinases

Abstract: Fibrosis can occur in many organs, where it is a debilitating and preneoplastic condition. The senescence of activated fibroblasts has been proposed to ameliorate fibrosis via the innate immune system but its role in humans has not been investigated. The availability of oral submucous fibrosis (OSMF) biopsies at different stages of disease progression allowed us to test the hypothesis that senescent fibroblasts accumulate with the progression of human fibrosis in vivo, and also to examine the mechanism of sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 46 publications
9
149
1
Order By: Relevance
“…We also reported previously that the intracellular metabolic profile surprisingly showed a shift of energy metabolism away from the tri-carboxylic acid (TCA) cycle and towards glycolysis and the pentose phosphate pathway23 and more recent evidence suggests that the shift to glycolysis may dependent on mitochondrial dysfunction24. In addition, we reported evidence of a strong redox homeostasis response that is consistent with relatively low levels of cells positive for nuclear 8-hydroxy-2-deoxyguanosine compared to DNA damage foci in established PEsen cells2325.…”
supporting
confidence: 78%
“…We also reported previously that the intracellular metabolic profile surprisingly showed a shift of energy metabolism away from the tri-carboxylic acid (TCA) cycle and towards glycolysis and the pentose phosphate pathway23 and more recent evidence suggests that the shift to glycolysis may dependent on mitochondrial dysfunction24. In addition, we reported evidence of a strong redox homeostasis response that is consistent with relatively low levels of cells positive for nuclear 8-hydroxy-2-deoxyguanosine compared to DNA damage foci in established PEsen cells2325.…”
supporting
confidence: 78%
“…Furthermore it was observed that the senescent fibroblasts produce 25-83 times more MMP-1 and -2 than their pre-senescent counterparts. Therefore, senescent cells may locally ameliorate the fibrosis by increased expression of MMPs prior to their clearance by the innate immune system [75]. Although, our two studies show slightly different findings in relation to senescence and arecoline, increase amount of senescent cells appeared to be common.…”
Section: Senescence and Epithelial Mesenchymal Interactionscontrasting
confidence: 54%
“…Significance of ROS in the pathogenesis and malignant transformation of OSF. 55 has been highlighted.…”
Section: Mechanisms Of Pathogenesis Of Oral Submucous Fibrosis Changementioning
confidence: 99%